2009
DOI: 10.2147/vhrm.s6269
|View full text |Cite
|
Sign up to set email alerts
|

Lipoprotein ratios: Physiological significance and clinical usefulness in cardiovascular prevention

Abstract: Low-density lipoprotein (LDL) cholesterol concentration has been the prime index of cardiovascular disease risk and the main target for therapy. However, several lipoprotein ratios or "atherogenic indices" have been defined in an attempt to optimize the predictive capacity of the lipid profile. In this review, we summarize their pathophysiological aspects, and highlight the rationale for using these lipoprotein ratios as cardiovascular risk factors in clinical practice, specifying their cut-off risk levels and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
95
0
9

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 314 publications
(107 citation statements)
references
References 53 publications
3
95
0
9
Order By: Relevance
“…The non-significant decrease in TC by 2.7L% observed in this study contrasts the significant increase in TC observed in an aerobic exercise training group of elderly postmenopausal women (Fahlman, Boardley, Lambert, & Flynn, 2002 Total cholesterol to HDL ratio (cardiovascular risk ratio) has a greater predictive capacity than the isolated components of lipid profile which could be a sensitive and specific index of cardiovascular risk. A study concluded after sensitivity analyses that, aerobic exercise only increases HDL-C while decreasing the cardiovascular risk ratio in older adults (Millan et al, 2009) (Utian, 2007). There is also no significant difference in the health QoL between EG and CG before the intervention contrary to the significantly higher difference in the EG after 8 weeks when compared to the CG.…”
Section: Resultsmentioning
confidence: 99%
“…The non-significant decrease in TC by 2.7L% observed in this study contrasts the significant increase in TC observed in an aerobic exercise training group of elderly postmenopausal women (Fahlman, Boardley, Lambert, & Flynn, 2002 Total cholesterol to HDL ratio (cardiovascular risk ratio) has a greater predictive capacity than the isolated components of lipid profile which could be a sensitive and specific index of cardiovascular risk. A study concluded after sensitivity analyses that, aerobic exercise only increases HDL-C while decreasing the cardiovascular risk ratio in older adults (Millan et al, 2009) (Utian, 2007). There is also no significant difference in the health QoL between EG and CG before the intervention contrary to the significantly higher difference in the EG after 8 weeks when compared to the CG.…”
Section: Resultsmentioning
confidence: 99%
“…Many studies reported the importance of many lipid ratios or atherogenic indexes. These indexes were strong indicators of the CVD risk by its expressions of imbalance between atherogenic and antiatherogenic lipoproteins [43, 44]. Atherogenic index of plasma (AIP) has emerged as a predictive marker for plasma atherogenicity [45].…”
Section: Discussionmentioning
confidence: 99%
“…These ratios are now recognized to be independently associated with cardiovascular disease risks [18,19]. When published cut-offs for unfavorable risk categories associated with poor cardiorespiratory fitness and cardiovascular disease were considered [18][19][20], 44% of the males and 39% of the females had values above the cut-offs for TC/HDL baseline ratios (above 5.0 and 4.5, respectively) suggesting that these individuals are at substantial metabolic risks. Similarly, with 3.5 and 3.0 cut-offs for LDL/HDL for males and females respectively, 33% of males and 35% of females in this study had higher values, and with the absolute means far above the cut-offs.…”
Section: Discussionmentioning
confidence: 99%
“…Cardio-metabolic characteristics are also used to assess disease risk across all ages. Reference cut-offs have been published for blood lipid profiles and ratios for unfavorable health risks associated with poor cardiorespiratory fitness and cardiovascular disease [18][19][20]. Other physiognomies for estimation of metabolic risks and disease, for which cut off points are known, include fasting blood sugar, blood pressure (BP) and pulse rates (HR) [12,21].…”
Section: Introductionmentioning
confidence: 99%